THE ROLE OF BRAND IMAGE, PRICE, PACKAGING, PRODUCT QUALITY, AND WORD OF MOUTH ON THE INTEREST IN PURCHASING TORIYU BRAND BOTTLED DRINKING WATER PRODUCTS (AMDK) IN YOGYAKARTA - Yunus Indra Purnama (ZILLZELL MEDIA PRIMA, 2024)
The large number of businesses in the Bottled Drinking Water (AMDK) industry results in fierce competition with one of the main factors affecting is price. In addition to price, packaging is also important because it makes a first impression. Quality must be considered because together with price and packaging can create a good brand image that encourages the creation of word of mouth which can be a strength in itself. The purpose of the study is to determine the influence of price, product quality, brand image and word of mouth on the buying interest of Toriyu brand bottled water products, in students of the Faculty of Business and Humanities, Yogyakarta University of Technology (UTY). This study uses a Likert scale questionnaire. The data analysis technique is multiple regression using SEM-PLS. The sampling technique is accidental sampling, which is sampling is carried out spontaneously to anyone who is considered suitable. The research population is students of the Faculty of Business and Humanities, Yogyakarta University of Technology (UTY) with a total of 5,441 people, the sample used by 100 students based on the Slovin formula with an error rate of 5%. Based on the p values, it is known that Brand Image/Brand Image has a significant effect on buying interest, price has no effect on buying interest, packaging has a significant effect on buying interest, product quality has no effect on buying interest, Word of Mouth has a significant effect on buying interest.